1965
DOI: 10.1038/bjc.1965.47
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Carcinogenic Action of Certain Lactones and Related Substances in the Rat and Mouse

Abstract: On the other hand, in the lactones hitherto tested, absence of xfl-unsaturation, as in the fly-unsaturated a-angelica lactone and in the fully saturated y-butyro lactone, or opening of the lactone ring by hydrolysis, resulted in loss of carcinogenicity.In the case of the remarkably highly carcinogenic unsaturated lactone represented by the mould-product aflatoxin, the chemical structure of this compound was not known at the time when groundnut meal infected with Aspergillus fiavus was first shown to constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…This toxin has antibiotic activity, is toxic to animals (Hooper et al 1944;Norstadt & McCalla, 1968) and is carcinogenic in rats and mice (Dickens & Jones, 1961, 1965. As for mode of action, Jones & Young (1968) suggested that the SH group of thiol enzymes reacts with the double bond conjugated to the lactone carbonyl group of patulin, and Atkinson & Stanley (1943) suggested that the antibiotic activity of patulin may be due to its reaction with SH groups of microbial enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…This toxin has antibiotic activity, is toxic to animals (Hooper et al 1944;Norstadt & McCalla, 1968) and is carcinogenic in rats and mice (Dickens & Jones, 1961, 1965. As for mode of action, Jones & Young (1968) suggested that the SH group of thiol enzymes reacts with the double bond conjugated to the lactone carbonyl group of patulin, and Atkinson & Stanley (1943) suggested that the antibiotic activity of patulin may be due to its reaction with SH groups of microbial enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The cis-unsaturated analogs, such as mucochloric acid (Mowry, 1950), penicillic acid (Birkinshaw et aL, 1936) and 4-oxypentenoic acid derivatives (Sheffold & Dubs, 1967) have open-cyclic equilibria which favor the cyclic forms. In the case of penicillic acid, the cyclic lactol form is given credit in part for its carcinogenic .activity (Dickens, 1964(Dickens, , 1965. Among the aromatic analogs, the 'hydroxyphthalide' or cyclic structures of 2methanoylbenzoic acids were assigned by de Diesback & Riat (1937), and the cyclic forms of 2-methanoyl-and 2-ethanoylbenzoic acid could be inferred from lowresolution NMR spectra in solution and their solid-state IR spectra (Tyman & Najam, 1977).…”
mentioning
confidence: 99%
“…Since the Penicillia are commonly found in/on foods and feeds, and are of considerable importance in production of cheeses and sausages, an intensive search for these mycotoxins was made, starting with patulin and penicillic acid. These two mycotoxins had been shown (Dickens and Jones 1965) to cause tumours in mice on subcutaneous injection. Given orally, patulin does not appear to be carcinogenic.…”
Section: A E Pohlandmentioning
confidence: 99%